Supraspinal effects of dorsal root ganglion stimulation in chronic pain patients - Parker, T; Huang, Y; Raghu, ALB; FitzGerald, J; Aziz, TZ; Green, AL (Wiley, 2021)
Objectives: Dorsal root ganglion stimulation (DRGS) has become a popular neuromodulatory treatment for neuropathic pain. We used magnetoencephalography (MEG) to investigate potential biomarkers of pain and pain relief, based on the differences in power spectral density (PSD) during varying degrees of pain and how these oscillations change during DRGS-mediated pain relief.